A Semi-Empirical Method for Modeling Reciprocating Compressors in Residential Refrigerators and Freezers - Jaehnig, Dagmar (University of Wisconsin-Madison, 1999)
Calorimeter testing data for domestic refrigerator/freezer compressors have been collected. The current method to represent compressor performance data recommended by the Air-Conditioning and Refrigeration Institute (ARI) has been applied to all experimental data. It has been found that the model does not reliably interpolate and extrapolate. A semi-empirical model to represent compressor performance has been developed. The model is based on the concept of volumetric efficiency and assumes a polytropic compression process. The model contains 5 curve fit parameters that have to be determined with non-linear regression. A minimum of 4 measurements of mass flow rate and electrical power are necessary to generate accurate compressor maps with this model. The model has been shown to extrapolate within 5% error to 10C higher and lower condensing and evaporating temperatures than represented in the measured data. The effect of a change in ambient temperature has been compared with data available in the literature and seems well represented in the model as a change in the suction temperature.
Under the supervision of Professors Sanford Klein and Douglas Reindl; 289pp.
Keywords: Thesis (M.S.)--University of Wisconsin--Madison, 1999.; Dissertations Academic Mechanical Engineering.; University of Wisconsin--Madison. College of Engineering.